EnDovascular Therapy Plus Best Medical Treatment (BMT) Versus BMT Alone for MedIum distal VeSsel Occlusion sTroke (DISTAL) - Marios-Nikos, Psychogios (2024)
Funding Information: The author(s) disclosed receipt of the following financial support for the research, authorship, and/or publication of this article: The trial is supported by public grants from the Swiss National Science Foundation (SNSF grant number 33IC30_198783) and the Gottfried und Julia Bangerter-Rhyner-Stiftung (Basel, Switzerland) as well as through unrestricted grants from Stryker Neurovascular Inc., Medtronic Inc., Phenox GmbH, Rapid Medical Inc., and Penumbra Inc.. The funders had no role in the design, site selection, planning or conduct of the trial and they will have no role in the analysis of the trial data, the writing of the manuscript or the interpretation of the trial data. Funding Information: Jens Fiehler: Research support: German Ministry of Science and Education (BMBF), German Ministry of Economy and Innovation (BMWi), German Research Foundation (DFG), European Union (EU), Hamburgische Investitions- und F\u00F6rderbank (IFB), Medtronic, Microvention, Route92, Stryker. Consultant for: Acandis, Bayer, Cerenovus, Covidien, Medtronic, Microvention, Penumbra, Phenox, Roche, Stryker, TG Medical. Stockholder: Tegus Medical, Eppdata, Vastrax. Funding Information: Urs Fischer: Research support of the Swiss National Science Foundation and the Swiss Heart Foundation; PI of the ELAN trial, Co-PI of the DISTAL, TECNO, SWIFT DIRECT, SWITCH, ELAPSE and ICARUS trial; research grants from Medtronic (BEYOND SWIFT, SWIFT DIRECT), from Stryker, Rapid medical, Penumbra, Medtronic and Phenox (DISTAL), and from Boehringer Ingelheim (TECNO), whereas all fees were paid to the institution; consultancies for Medtronic, Stryker, and CSL Behring (fees paid to institution); participation in an advisory board for Alexion/Portola, Boehringer Ingelheim, Biogen and Acthera (fees paid to institution); member of a clinical event committee (CEC) of the COATING study (Phenox) and member of the data and safety monitoring committee (DSMB) of the TITAN, LATE_MT and IN EXTREMIS trials; presidency of the Swiss Neurological Society. Funding Information: Marios Psychogios: Grants from the Swiss National Science Foundation (SNF) for the DISTAL trial (33IC30_198783), ICARUS (32003B_220118) and TECNO trial (32003B_204977), Grant from Bangerter-Rhyner Stiftung for the DISTAL trial. Unrestricted Grants for the DISTAL trial from Stryker Neurovascular Inc., Medtronic Inc., Phenox GmbH, Penumbra Inc. and Rapid Medical Inc., Sponsor-PI SPINNERS trial (Funded by a Siemens Healthineers AG Grant), Research agreement with Siemens Healthineers AG, Local PI for the ACT in STROKE, ASSIST, EXCELLENT, TENSION, COATING, SURF and ESCAPE-NEXT trials. Speaker fees: Stryker Neurovascular Inc., Medtronic Inc., Penumbra Inc., Acandis GmbH, Phenox GmbH, Siemens Healthineers AG. Publisher Copyright: © European Stroke Organisation 2024.